Reading learning centers for the primary grades : - Wait, Shirleen (Jossey-Bass, 2005)
The book includes information on topics such as the types of centers that match various learning styles and ability levels, directions for organizing and managing the centers, ideas for establishing monthly themes, and directions for creating hands-on skills games for remediation and enrichment. The book contains thirteen seasonal themes, lists of thematic children's books, calendars and bulletin-board ideas, and illustrated, step-by-step directions for creating 88 thematic and skills-based board, card, sorting, and matching games. This new edition addresses No Child Left Behind legislation and standards, and reflects the diverse U.S. population through Black History, Hispanic, Asian, and Classical Latin cultural themes.